Sedimentology and Stratigraphy of an Upper Permian Sedimentary Succession: Northern Sydney Basin, Southeastern Australia - Sean Melehan; Chrysanthos Botziolis; Angelos G. Maravelis; Octavian Catuneanu; Kevin Ruming; Erin Holmes; William J. Collins (Geosciences, 2021)
This study integrates sedimentological and stratigraphic insights into the Upper Permian sedimentary rocks of the Wittingham, Tomago and Newcastle Coal Measures in the Northern Sydney Basin, Australia. Facies analysis documented fifteen facies that belong to seven facies associations. These facies associations correspond to different depositional environments and sub-environments including prodelta, delta-front, upper, lower delta-plain and fluvial. The stratigraphic development points to a shallowing upward trend and is reflected with fluvial deposits sitting on top of the deltaic deposits. The fluvio-deltaic contact is represented by an unconformity and displays an upward increase in sediment caliber. The delta front is mainly controlled by wave, storms- and/or river currents, even though the contribution of tides also occurs in the form of sedimentary structures that suggest tidal influence. In contrast, prodelta and delta-plain are significantly modulated by tidal currents. The impact of tides in the delta plain is fading away upward and therefore, the upper delta plain is much less impacted compared to the lower delta plain. The low abundance of wave ripples suggests that the wave action was not very important in the delta plain. Steep topographic gradients and increased sediment input are suggested, based on the limited or absent evidence of tides in the fluvial realm, related to the growing New England Orogen. In sequence stratigraphic terms, the deltaic system accumulated during highstand normal regression, while the deposition of the overlying fluvial system occurred during lowstand normal regression. The two systems are separated by a subaerial unconformity developed during an intervening forced regression. Short periods of transgression are inferred from the presence of higher frequency cycles in the delta-front.